Evaluating Public Awareness of Environmental Management Strategies for Malaria Control and Prevention: A Case Study of Michika Local Government Area - Isaac John Umaru; Solomon O. Asare; Tyem Lawal Danjuma; Usenobong Morgan Akpan; Ingwu Joseph Akem; Emmanuel Olofu Omanchi; Julius Ishaya Salman; Kwabena Owusu Amoah; Maryam Usman Ahmed; Hauwa A. Umaru (African Journal of Clinical Medicine and Pharmacy Research, 2026)
This study investigated malaria awareness, environmental risk factors, and preventive practices among adult residents of Michika Local Government Area, Adamawa State, Nigeria. A mixed-methods approach was employed, combining structured questionnaires, key informant interviews, and field observations to generate comprehensive data. Using a multistage sampling technique, 300 adult participants were selected across five wards to ensure representative coverage. The questionnaire was pre-tested for clarity and reliability, yielding a Cronbach’s alpha of 0.78. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The findings revealed high levels of malaria awareness, with more than 90% of respondents identifying mosquito bites as the primary mode of transmission; however, misconceptions such as attributing malaria to dirty water and contaminated food persisted. Environmental risk factors were widely recognized, particularly stagnant water, poor drainage, and open waste disposal, and field observations confirmed the presence of these conditions, especially in Michika I, which recorded the highest prevalence of stagnant water (88%) and blocked drainage (75%). Preventive practices varied across respondents, with mosquito net use emerging as the most common measure, reaching up to 80% in Michika I, whereas participation in community sanitation remained moderate. Perceptions of institutional responses were mixed, as only 50% of respondents in Michika I believed that government efforts to control malaria were adequate. These findings indicate that, despite strong individual awareness and relatively positive preventive behavior, persistent environmental challenges, limited community engagement, inadequate funding, poor infrastructure, and low participation continue to constrain malaria control efforts. The study underscores the need for integrated strategies that combine public education, environmental remediation, and multi-sectoral collaboration, and it provides an empirical basis for targeted policy interventions and future research on sustainable malaria control in Michika and comparable settings.